Ovarian function in Samoan women shows stronger association with signals of energy metabolism than fat reserves. Issue 1 (15th October 2013) - Sherry, Diana S.; Mcgarvey, Stephen T.; Sesepasara, Margaret L.; Ellison, Peter T.
<x xml:space="preserve">Abstract</x> Objectives The relative influence of prominent energetic hormones such as insulin and leptin on ovarian steroid production has yet to be determined and demonstrated consistently in vivo. This study reports preliminary findings on the relationship between insulin, leptin, and estradiol, a major ovarian steroid, in a sample of Samoan women. Methods Participants were 34 regularly cycling, nonlactating, premenopausal women in the follicular phase of their menstrual cycle with indicators of normal glucose tolerance. Fasting serum samples provided one‐time, cross‐sectional measures of glucose, insulin, leptin, and estradiol. Main statistical analyses consisted of Student's t‐tests, used to determine significant differences in mean estradiol level between contrasting groups of insulin and leptin. Results Relatively high insulin levels within the normal range of variation showed a positive association with estradiol levels whereas relatively high leptin levels did not. The association between insulin and estradiol appeared to conform to a step‐like categorical relationship—with the highest insulin levels exerting the greatest positive effect—rather than a dose‐response linear relationship. Conclusions This study adds to the growing evidence that peripheral regulation of ovarian function likely involves permissive signals that emphasize a state of energy surplus, related primarily to energy metabolism rather than energy reserves, and warrant more extensive study. Am. J. Hum. Biol. 26:95–98, 2014. © 2013 Wiley Periodicals, Inc.